Clinical outcome of childhood lymphoblastic lymphoma in Shanghai China 2001–2010. Issue 4 (14th November 2013) - Gao, Yi‐Jin; Pan, Ci; Tang, Jing‐Yan; Lu, Feng‐Juan; Chen, Jing; Xue, Hui‐Liang; Zhai, Xiao‐Wen; Li, Jun; Ye, Qi‐Dong; Zhou, Min; Wang, Hong‐Sheng; Miao, Hui; et al.
Abstract Background This retrospective cohort study analysed the clinical characteristics and outcomes of patients with childhood lymphoblastic lymphoma (LBL) treated in Shanghai, China. Procedure From 2001 to 2010, 108 evaluable patients ≤16 years of age who were newly diagnosed with biopsy‐proven LBL were treated with one of three treatment protocols: CCCG‐99, SCMC‐T‐NHL‐2002, or LBL‐CHOF‐2006. Results Two patients had Stage I disease, 5 had Stage II, 55 had Stage III, and 46 had Stage IV. The immunophenotype was T‐cell LBL in 92 patients (85.2%) and precursor B‐cell LBL in 16 (14.8%). The abandonment rate was 11.5%. Twenty‐five patients (23.2%) suffered from resistant disease, including 1 with isolated central nervous system (CNS) relapse. At a median follow‐up of 40.4 months (range, 0–114 months), the 5‐year probability of event‐free survival (pEFS) was 63.9 ± 4.6% in all patients. The 5‐year pEFS for patients with pB‐LBL was better than for patients with T‐LBL (100% vs. 61.3 ± 5.1%, P = 0.007). Patients who had achieved complete remission on day 33 of induction had significantly better pEFS than those who had not (78.8 ± 4.6% vs. 28.2 ± 9.0%, P = 0.000). Three of 25 patients who experienced resistant disease were alive at the end of the study period. Conclusions The abandonment rate was lower for patients with LBL than for patients with acute lymphoblastic leukemia. Prophylactic cranial radiation can be omitted for patients with LBL even when advanced‐stage disease is present, as intensive systemic chemotherapy with intrathecal therapy is sufficient to prevent CNS relapse. The survival of patients with resistant disease was very poor. Pediatr Blood Cancer 2014;61:659–663. © 2013 Wiley Periodicals, Inc.